2019
DOI: 10.1038/s41598-019-55005-0
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy vulnerability in urban areas: a pragmatic approach combining behavioral, medico-obstetrical, socio-economic and environmental factors

Abstract: Multiple risk factors are associated with adverse pregnancy outcomes (APO), but how all these different factors combine and accumulate remains unknown. The objective of this observational retrospective study was to describe the accumulation of multiple vulnerability markers in pregnant women living in an urban area. Women living in Besançon (France) who delivered between 2005 and 2009 were included. Individual data were collected from the obstetrical records while environmental exposures were collected using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As such, based on the French Health Authority's recommendations [ 17 ] and the Canadian study on indigenous women [ 30 ], we can confirm the importance of a single trusted contact person to optimise the coordination of prenatal care. Other international studies about the care of vulnerable pregnant women do not specifically recommend the place of this support person [ 16 , 20 , 21 , 23 , 26 ]. However, an analysis of the recommendation for having personalised care in proximity to the vulnerable pregnant woman's culture corresponds to our findings, ensuring a single trusted contact person.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, based on the French Health Authority's recommendations [ 17 ] and the Canadian study on indigenous women [ 30 ], we can confirm the importance of a single trusted contact person to optimise the coordination of prenatal care. Other international studies about the care of vulnerable pregnant women do not specifically recommend the place of this support person [ 16 , 20 , 21 , 23 , 26 ]. However, an analysis of the recommendation for having personalised care in proximity to the vulnerable pregnant woman's culture corresponds to our findings, ensuring a single trusted contact person.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these plans, the international literature indicates there is room for improvement in the support and care of pregnant women in vulnerable situations. Professionals need to identify vulnerable pregnant women and facilitate their access to care [ 16 , 20 , 21 ]. Currently, there are quantitative epidemiological studies evaluating the effectiveness of perinatal measures [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental residential exposures. The residential exposure assessments have been previously described 10,[33][34][35][46][47][48][49][50] . The participants' addresses at the date of delivery were extracted from CPage software (ver-sion 2, https:// www.…”
Section: Covariablesmentioning
confidence: 99%
“…Several studies have demonstrated that vulnerability markers predict the risk of adverse pregnancy outcomes (Brembilla, et al 2019, Posthumus, et al 2016. Brembilla, et al (2019) showed that vulnerability markers tend to accumulate, and are subsequently associated with an increased risk of adverse pregnancy outcomes (Brembilla, et al 2019).…”
Section: Introductionmentioning
confidence: 99%